2012
DOI: 10.1021/jm201310y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure–Activity Relationship of Potent and Selective Covalent Inhibitors of Transglutaminase 2 for Huntington’s Disease

Abstract: Tissue transglutaminase 2 (TG2) is a multifunctional protein primarily known for its calcium-dependent enzymatic protein cross-linking activity via isopeptide bond formation between glutamine and lysine residues. TG2 overexpression and activity have been found to be associated with Huntington's disease (HD); specifically, TG2 is up-regulated in the brains of HD patients and in animal models of the disease. Interestingly, genetic deletion of TG2 in two different HD mouse models, R6/1 and R6/2, results in improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 47 publications
1
67
1
Order By: Relevance
“…18 In addition, we have reported potent and selective covalent inhibitors bearing an acrylamide warhead as in 1 (Figure 1). 19 Compound 1 has TG2 IC 50 of 0.11 μM; however, in vitro metabolism profiling studies identified plasma stability as an issue cautioning against in vivo evaluation. Compound 1 was one of the examples showing better stability in plasma, having a half-life of 209 min in mouse plasma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 In addition, we have reported potent and selective covalent inhibitors bearing an acrylamide warhead as in 1 (Figure 1). 19 Compound 1 has TG2 IC 50 of 0.11 μM; however, in vitro metabolism profiling studies identified plasma stability as an issue cautioning against in vivo evaluation. Compound 1 was one of the examples showing better stability in plasma, having a half-life of 209 min in mouse plasma.…”
mentioning
confidence: 99%
“…Our working hypothesis regarding the mode of binding of these compounds remained consistent with our prior modeling and SAR studies (Figure 2). 19 Key interactions are capture of the acrylamide by Cys277 accompanied by additional acrylamide hydrogen-bonding interactions with the side chains of Trp241 and Gln276. In addition, there is a potential hydrogen-bonding interaction of the sulfonyl with the side chain of Asn333, which may facilitate further interactions with residues Leu312, Phe316, Ile331, and Leu420 that line an adjacent lipophilic pocket.…”
mentioning
confidence: 99%
“…ZDON was protective in several in vitro and in vivo models of HD and it inhibited a-synuclein aggregation in a PD model, but the high concentrations needed to exert protection in vitro make it a poor therapeutic candidate for in vivo studies. Similarly, many other compounds developed 36,104 are useful chemical biology tools in vitro but do not meet the standards to be translated in vivo for animal studies, and by extension for human therapeutics.…”
Section: Therapies and State Of Art For Inhibitorsmentioning
confidence: 99%
“…Previous reports related to this type of transformations have appeared in the literature, but they have been only briefly investigated. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Activation methods have found the reagents to be resistant to amide formation of 2-aminopyrimidines with low or moderate yields. [11][12][13][14] By the addition of the appropriate benzoyl chloride to 2-amino-4-(3-pyridinyl)pyrimidine in refluxing pyridine, 6 a group of N-mono-and N,N-dibenzoyl derivatives has been prepared in low yield.…”
Section: Introductionmentioning
confidence: 99%
“…The same mixture of N-monobenzoyland N,N-dibenzoyl-2-aminopyrimidines has been obtained (15% and 45%, respectively) by reaction of the 2-aminopyrimidine scaffold with benzoyl chloride in refluxing dichloromethane 15 and excess pyridine for 48 h. Peracylation of a 2,4-diaminopyrimidine-derivative has also been obtained with excess of benzoyl chloride in pyridine at room temperature for 18 hours, 16,17 while N,N-dibenzoyl-deoxycytidine has been formed as a by-product in the N-benzoylation of deoxycytidine 18 and 2-aminopyridines. 19 Finally, 2-N-pyrimidinyl acrylamide has been prepared under forcing conditions (NaH/THF) from acryloyl chloride in modest yield. 20 Acetylation of 2-amino-phenylpyrimidines with acetic anhydride has given both the monoand di-acetylated products, [21][22][23][24][25] which were easily converted into N-monoacylated by treatment in basic medium.…”
Section: Introductionmentioning
confidence: 99%